Pyridine and pyridinone-based factor XIa inhibitors. Issue 4 (15th February 2015) - Corte, James R.; Fang, Tianan; Hangeland, Jon J.; Friends, Todd J.; Rendina, Alan R.; Luettgen, Joseph M.; Bozarth, Jeffrey M.; Barbera, Frank A.; Rossi, Karen A.; Wei, Anzhi; Ramamurthy, Vidhyashankar; Morin, Paul E.; et al.
Graphical abstract